Desechos tóxicos nitrogenados y su incidencia en la oxidación de amonio a nitrito y de nitrito a nitrato - Bravo Vargas, John Richard (2010)
The initial period of this investigation was carried out in Mr. Miguel's Pine grove camaronera, located in Puerrto Jelí, canton Santa Rosa, i El Oro province. Later it was carried out at the laboratories of the Faculty of Agropecuary Sciences belonging to the Technical University of Machala. Their objective was to evaluate the higher increase of bacterias nitrifyng obtained in each of different phases or steps of oxidation. It was used as nutrient media ammonium chloride, sodium nitrite and oligoelementos, with three levels of calcium carbonate. The study consisted of: 3 treatments, 3 blocks and 3 reapplications for each one of the steps, giving a total of 27 experimental units or samples for each step. The obtained data were analyzed with an ANOVA of 2 ways with interaction to detect significant differences. The inóculo for the cultivar was of 28 000 UFC/ml of BOA (bacterias ammonium oxidizers) and of 86 000 UFC/ml of BON (bacterias nitrite oxidizers). The bacterial counting for all cultivars was carried out at 15 days with the more probable number method (NMP). Biostatistically for the BOA, the levels of ammonium chloride used in the bioassay have not significance (they do not influence in the population increase of bacterias), but there is interaction between the chloride and the calcium carbonate (they do influence on the bacterial increase). The levels of sodium nitrite used in second oxidation are of significance, they do influence on the bacterial increase. There is a relationship among the levels of nitrito sodium and the levels of calcium carbonate with a significance on increase of BON.